PhenoTips: Patient Phenotyping Software for Clinical and Research Use. Issue 8 (24th May 2013) - Girdea, Marta; Dumitriu, Sergiu; Fiume, Marc; Bowdin, Sarah; Boycott, Kym M.; Chénier, Sébastien; Chitayat, David; Faghfoury, Hanna; Meyn, M. Stephen; Ray, Peter N.; So, Joyce; Stavropoulos, Dimitri J.; et al.
<x xml:space="preserve">Abstract</x> PhenoTips is an open source software package for collecting and analyzing phenotypic information for patients with genetic disorders. Our tool closely mirrors clinician workflows, facilitating the recording of observations during the patient encounter. Its easy‐to‐use interface, compatible with any device that runs a Web browser, is coupled with a standardized database where phenotypic information is represented using the Human Phenotype Ontology. In addition to data collection, PhenoTips analyzes a wide range of measurements, and provides exam and diagnosis assistance <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>